1976
DOI: 10.1104/pp.57.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase Regulation by Energy Charge in Sunflower Roots

Abstract: Energy charge I(ATP) + 1/2 (ADP)J/[(ATP) + (ADP) + (AMP)]and glutamine synthetase activity (transferase reaction) of roots increase in a near congruent manner when decotyledonized sunflower plants (Helianthus annuus L. var. Mammoth Russian) are grown in nitrate for 9 days. Replacement of nitrate with ammonium for the final 2 days leads to a higher energy charge and increased enzyme activity. Similar (20,23,28). An enzyme utilizing the energy of ATP in bond formation is glutamine synthetase (EC 6.3.1.2.). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
1

Year Published

1977
1977
1988
1988

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…GS, as an enzyme utilizing the energy of the anhydride phosphate bond in a synthetic reaction, might thus be expected to be influenced by the energy charge of the cell. All data of the present study confirm the findings of previous studies with sunflower roots (34) indicating a direct correlation between energy charge and GS activity (Figs. 1-4).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…GS, as an enzyme utilizing the energy of the anhydride phosphate bond in a synthetic reaction, might thus be expected to be influenced by the energy charge of the cell. All data of the present study confirm the findings of previous studies with sunflower roots (34) indicating a direct correlation between energy charge and GS activity (Figs. 1-4).…”
Section: Discussionsupporting
confidence: 83%
“…The high degree of correlation between GS activity and the energy level of sunflower root tissue noted in a previous study (34) was also found in the present investigation. For both entrainment and continuous light free-running periods, L12:D12 plants subjected to a 6 AM on-6 PM off regimen displayed a rhythm of approximately 12 h for energy charge that was directly correlated in time with the rhythmic activity of GS (Fig.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…As shown in Table II, assimilation of inorganic N was much affected by NaCl, an observation which is consistent with results of Helal and Mengel (5) obtained from young barley plants. This effect is related to glutamine synthase, whose activity depends much on energy supply (19).…”
Section: Discussionmentioning
confidence: 99%
“…GS is associated with chloroplasts and requires ATP in order to assimilate ammonium. The enzyme is known to be especially sensitive to small changes in adenylate energy charge (25,26), and, in this scheme, ATP is supplied to the enzyme by photophosphorylation. When the cell is not light limited, sufficient ATP supply is maintained for high GS activity.…”
Section: Introductionmentioning
confidence: 99%